Inquiry Based Teaching in Writing Classroom: the Effectiveness to the Students’ Creativity - Fitria Wulan Sari (STKIP AL HIKMAH SURABAYA, 2020)
The main objectives of the research are to find out whether (1) Inquiry Based Teaching is more effective than Guided Writing to teach writing skill; (2) Students having high creativity have better writing skill than those having low creativity; and (3) there is any interaction between teaching methods and students’ creativity in teaching writing skill for students. The research applied in this research was an experimental research. The teaching methods are Inquiry Based Teaching and Guided Writing. Creativity as the attributive variable was divided into high creativity and low creativity. The population of the research was the students of junior high school consisting of 176 students. The samples of this research were the class 8B as experimental class and 8A as control class that consisted of 22 students in each class. The result of data analysis shows that; (1) Inquiry Based Teaching is more effective than Guided Writing to teach writing skill; (2) Students having high creativity have better writing skill than those having low creativity; and (3) There is an interaction between teaching methods and students’ creativity to teach writing skill for the students. Based on the research findings, it can be concluded that Inquiry Based Teaching is an effective method to teach writing skill, and the effectiveness is affected by the degree of students’ creativity .